Análisis bibliométrico sobre estudios de inteligencia artificial en neoplasias en latinoamérica - Ruiz Lazo, Mayer John (2024)
Objective: To analyze the scientific production on artificial intelligence in neoplasms in the Latin American region by exploring records in the Virtual Health Library and Scopus databases from 1990 to December 2022. Method: A descriptive research study with a cross-sectional, quantitative, and bibliometric design. Results: The BVS and Scopus have been instrumental in gathering scientific production on artificial intelligence applied to neoplasms. We found a total of 232 articles between 1990 and 2022, with a significant increase in publications observed, reaching a peak of 52 studies in 2022. Journals such as "Computers in Biology and Medicine" and "Artificial Intelligence in Medicine" stand out as leaders in disseminating research in Latin America. Brazil leads collaboration in the region, followed by South American countries like Colombia. Furthermore, active international collaboration is evident, promoting knowledge exchange. Institutions in Brazil and Colombia lead scientific production in the region, suggesting robust research activity at the intersection of artificial intelligence and neoplasms. Conclusions: Research on artificial intelligence applied to neoplasms in Latin America has grown considerably up to 2022, led by Brazil, Colombia, and Mexico, with notable international collaboration. Studies focus on diagnostic accuracy and image analysis, especially in magnetic resonance imaging and mammography.